The Seven Standards of Textuality in News Texts: A Discourse Analysis - Rahma, Alya; Chelsea , Julian; Agustina, Imas Wahyu (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2022)
The textuality of a text is important to decide whether a text could be considered a textual text or not. This study examines the textuality of some news articles about a recent trending topic that has drawn the world’s attention as it took many people’s lives: the Kanjuruhan tragedy. The data of this study were words, phrases, and sentences taken from five news articles which were then analyzed using de Beaugrande and Dressler’s theory concerning the seven standards that make a text considered acceptable or unacceptable in terms of textuality. The study revealed that those five texts have fulfilled all standards of textuality, which cover Cohesion, Coherence, Intentionality, Acceptability, Informativity, Situationality, and Intertextuality. Thus, those five articles can be considered trustworthy texts.